The suffering of the migrant: Cuban migration and the Ecuadorian dream of free human mobility - Freier, Luisa Feline (2019)
This paper explores the tension between the concept of suffering  as employed in the humanist migration discourse of Rafael Correa and  the migratory experience of Cuban immigrants in Ecuador. Despite the former president’s revolutionary discourse, Cuban migrants face triple discrimination:  social, economic and legal, in the context of both Ecuadorian  and Cuban migration policies. This study contributes to the literature on migration and suffering, as well as  the emerging literature on the discursive  gaps inherent in Latin American immigration policy liberalization.